Pendampingan Orang Tua dan Pengaruhnya terhadap Minat Belajar Baca Tulis Alquran Siswa MIN 1 Dairi - Muhammad Sanif (Departement of Mathematics Education, 2024)
This research aims to identify the low level of parental assistance to children, the lack of parental attention which makes children's interest and enthusiasm for learning low and the low interest in learning to read and write the Quran due to lack of assistance from parents. This research is quantitative research. This research uses a